Daily supplementation of lesser mealworm protein for 11-weeks increases skeletal muscle mass in physically active older adults - Lotte Koopmans; Marcia Spoelder; Coen C.W.G. Bongers; Thijs M.H. Eijsvogels; Maria T.E. Hopman (Elsevier, 2024)
Background: Adequate protein intake is important to maintain skeletal muscle mass in older adults and to prevent sarcopenia. Insect-based supplements were recently introduced to the market as an environmentally friendly protein alternative. We examined the effect of daily supplementation of lesser mealworm (Alphitobius diaperinus) protein for 11 consecutive weeks on muscle mass and muscle strength in older adults. Methods: In this randomized controlled trial, 70 physically active older adults (>60 years) were randomly allocated to three groups: (I) lesser mealworm protein, (II) whey protein or (III) iso-caloric placebo. Participants received 11 weeks of supplements two times a day (30 gram/day). Muscle mass, fat mass, leg muscle strength and handgrip strength were measured at baseline and after 11 weeks of supplementation. Results: Of the 70 participants, 59 completed the supplementation period (mealworm n = 16; whey n = 23; iso-caloric placebo n = 20). Overall, skeletal muscle mass increased from 29.0 ± 6.2 kg to 29.3 ± 6.1 kg, with a significantly more profound increase in the lesser mealworm group (+0.67 [0.20-1.14] kg) compared to the whey (+0.03 [-0.20 - 0.28] kg) and placebo group (+0.30 [0.03 - 0.63] kg, Pgroup*time = 0.030). Fat mass and maximum handgrip strength decreased over time, whereas one-repetition maximum (1RM) leg muscle strength did not change pre- versus post-intervention. No group differences, nor interaction effects, were observed for fat mass, leg muscle strength and handgrip strength Conclusion: 11-weeks of lesser mealworm protein supplementation induced an increase in skeletal muscle mass compared to whey protein supplementation and iso-caloric placebo in physically active older adults. No differences among groups were observed for changes in muscle strength.